EXPLORING LOCAL WISDOM-BASED MARKETING COMMUNICATION MODELS IN TOMALOU FISHERMEN'S VILLAGE FESTIVAL - Ariani Simabur, Lisda (PT. Sangadji Media Publishing, 2024)
The Tomalou Fishing Village Festival is one of the most significant cultural events in the Tidore Islands. This research aims to explore and analyze various dimensions of locally-based marketing communication models used to promote the festival. Through quantitative research methods, including in-depth interviews, participant observation, and content analysis, this study seeks to elucidate the effectiveness of these communication models in enhancing community engagement, fostering cultural appreciation, and attracting tourists to the Festival. Findings from this research give rise to a model called the Marketing Communication Model Rooted in Local Wisdom, which is expected to contribute to existing knowledge in cultural tourism, marketing communication, and community development.